The Representation of China's Leader in Media: A Critical Discourse Analysis - Atifah Nabila Nurfaiza; Indah Tasia Manuela S.; Aceng Ruhendi Saifullah (International Journal of Science and Society, 2026)
This study investigates the media representation of Chinese President Xi Jinping in a New York Times article titled “Trump’s Trade War Puts Bromance with Xi Beyond Reach” through Critical Discourse Analysis (CDA). Using van Dijk’s model, the research focuses on micro-level analysis, including macrostructure, microstructure, and superstructure. It applies linguistic tools such as actor description, level of description, and rhetorical devices. The findings reveal how the media constructs an image of Xi Jinping as an authoritarian leader with an anti-American stance and cautious diplomacy. The superstructure analysis highlights the use of subjective commentary and expert opinions, reinforcing a negative portrayal. This suggests ideological bias in Western media, particularly in how foreign leaders are depicted. The consistent negativity across macrostructure, microstructure, and superstructure reflects this tendency. The study emphasizes the role of discourse in shaping public opinion and recommends future comparative research on how U.S. leaders are portrayed in Chinese media to foster a more balanced understanding in global media narratives.